Sub-Saharan Africa : forging new trade links with Asia - Carey, Kevin, 1967-; Jacoby, Ulrich; Gupta, Sanjeev (Washington, DC : International Monetary Fund, 2007)
What is the impact on trade in sub-Saharan Africa of the recent rapid growth in China and other Asian countries, and the associated commodity price boom? This paper looks at how trading patterns (both destinations and composition) are changing in sub-Saharan Africa. Has the region managed to diversify the products it sells from commodities to manufactured goods? Has it expanded the range of countries to which it exports? And what about the import side? The time is ripe for sub-Saharan Africa to climb up the value chain of its commodity-based exports and to aim at an export surge based on labor-intensive manufacturing.
Evolution of Sub-Saharan African trade patterns through 2005 -- Benchmarking Sub-Saharan African trade performance -- Making trade and engine of development.
Includes bibliographical references (p. 51-55).
opc 13/03/15
Loans
Keywords: Africa, Sub-Saharan -- Foreign economic relations -- Asia; Asia -- Foreign economic relations -- Africa, Sub-Saharan.; Africa, Sub-Saharan -- Economic conditions